A network approach to analyse Australia's blue economy policy and legislative arrangements. (May 2023) - Frohlich, Miguel; Fidelman, Pedro; Dutton, Ian; Haward, Marcus; Head, Brian W.; Maynard, Dianne; Rissik, David; Vince, Joanna
Abstract: Governance systems are complex adaptive systems where multiple components interact extensively. This is the case for governance of the blue economy, focused on sustainable development of marine resources. Here, the relevant policy and legislative arrangements are fragmented, and marine uses, activities and resources are generally managed on a sectoral basis by independent entities from multiple jurisdictions. In Australia, for example, complex arrangements have created uncertainty in relation to what, when, how, and by whom blue economy activities are possible. Network approaches to map and analyse complex systems could potentially improve our understanding and facilitate management of policy and legal complexity. Yet, there are few studies that have adopted such approaches in ocean governance. Our research demonstrates the application of an innovative approach based on network graphs and text mining to analyse a policy and legislative system associated with Australia's blue economy (i.e., policy and legal arrangements applicable to the coastal and marine areas within the seaward boundaries of the continental shelf around the State of Tasmania). Using a database of over 2000 international, federal, state policy and legislative arrangements, cross-sector analyses were undertaken to identify potential gaps and overlaps that may hinder the deployment of blue economy activities, particularly those relating to integrated seafood and energy production systems. Our graphs allowed quick and easy visualisation of policy and legislative clusters around government entities, relationships between those entities and clusters, as well as potential gaps and overlaps in the existing policy and legislative landscape. Results point to a lack of integration and a need for fit-for-purpose policy and legislation, particularly for the development of co-located blue economy activities. Our approach may be used in research of other complex governance settings to inform policymaking as well as for communication and educational purposes. Highlights: Our network approach facilitates understanding of policy and legal complexity. The blue economy policy and legislative system in Tasmania, Australia, is analysed. Results show a need for greater integration and fit-for-purpose legislation. Regulatory complexity and fragmentation is very high for co-located activities.